Development of BRIGAVI SIPA as Learning Media Based on Picture Story Books and Videos about Pancasila Symbols and Their Application for First Grade Elementary School - Alifa Ambar Marwah; Dwi Nugroho Hidayanto; Sukriadi Sukriadi; Taufik Hidayat; Makmun Makmun (Journal of Educational Sciences, 2026)
This research is motivated by the limited availability of interesting reading materials for Pancasila Education. The learning process so far tends to rely on the use of textbooks provided by the government and student worksheets. Schools still show a low level of innovation and tend to be monotonous, resulting in limited student active involvement, with only a small number of students actively participating, while other students have not fully understood the material presented. This study aims to determine the development process, feasibility level, and practicality of BRIGAVI SIPA as a Picture Storybook-Based Learning Media and Videos on Pancasila Symbols and Their Application for Grade I Elementary School. The development was carried out using the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. The resulting products are five picture storybooks and learning videos. The feasibility results show that BRIGAVI SIPA as a learning media is in the very feasible category with a percentage of 95% by media experts, 97% by language experts, and 94% by material experts. The practicality test involved teachers and 16 grade I students, who each obtained a percentage of 91% and 97%, respectively, in the very practical category.